Application and discussion of the borehole radial deformation method in deep borehole geostress measurement - Han, Zengqiang; Li, Minghong; Wang, Chao; Wang, Jinchao; Huang, Xiaohua (Frontiers in Earth Science, 2023)
Geostress is an important parameter in rock related fields such as civil engineering, mining engineering and energy engineering. There are kinds of geostress measurement methods, however, many methods still have some limitations, especially when facing deep vertical boreholes. In this paper, we studied on the characteristics of borehole radial deformation under the action of geostress. First, the rule of borehole radial deformation under the action of two-dimensional geostress is studied, and the shape of borehole radial changes to ellipse under the action of geostress is proved. We derived the relationship between the magnitude of principal stresses and the parameters of borehole ellipse, revealed the rule that the principal axis direction of borehole ellipse is the direction of principal stress. That is the theoretical basis for the geostress calculation method based on borehole radial deformation measurement. Furthermore, we developed an apparatus that can simultaneously measure the changes of borehole diameters in multi-directions. The apparatus is designed with multi-contacts equidistant arrangement, micro-optical imaging measurement, electronic compass azimuth measurement, etc. It can adapt to the complex testing environment of deep boreholes and realize real-time monitoring of borehole deformation process. Indoor tests are carried out to verify the working performance of the apparatus. The results showed that measuring accuracy of the apparatus can reach 6.987μm, meeting the requirement of geostress measurement. Also, the results are well consistent with the loading force and direction of the testing machine. Field test was carried out in a deep borehole and the borehole radial deformation data was obtained in the process of stress relief. The feasibility of the instrument and method is verified by comparison with the hydraulic fracturing method. This paper provides a new idea and method for geostress measurement especially in deep vertical borehole.